Hypothalamic Mitochondrial Dysfunction as a Target in Obesity and Metabolic Disease - Cunarro, Juan; Casado, Sabela; Lugilde, Javier; Tovar, Sulay (Frontiers in Endocrinology, 2018)
Mitochondria are important organelles for the adaptation to energy demand that play a central role in bioenergetics metabolism. The mitochondrial architecture and mitochondrial machinery exhibits a high degree of adaptation in relation to nutrient availability. On the other hand, its disruption markedly affects energy homeostasis. The brain, more specifically the hypothalamus, is the main hub that controls energy homeostasis. Nevertheless, until now, almost all studies in relation to mitochondrial dysfunction and energy metabolism have focused in peripheral tissues like brown adipose tissue, muscle, and pancreas. In this review we highlight the relevance of the hypothalamus and the influence on mitochondrial machinery in its function as well as its consequences in terms of alterations in both energy and metabolic homeostasis.